Uso de relaves mineros provenientes de la planta de beneficio mineral “Reina del Cisne II, código 390015, cantón Portovelo, provincia de El Oro”, como agregado fino para la fabricación de bloques de tierra comprimida - Delgado Requena, Bryan Michael (2024)
The experimental project titled “Use of mining tailings from the Mineral Beneficiation Plant “Reina del Cisne II, code 390015”, Portovelo town, El Oro Province, as fine aggregate for the manufacture of Compressed Earth Blocks” was developed within the framework of the Engineering Degree in Environmental Geology and Territorial Planning, in search of sustainable alternatives that provide a solution to the final disposal of mining waste. To carry it out, a physical and chemical characterization of both the tailings sand and the soil from the neighborhood “Jardines de Punzara” was preceded. This allowed its classification according to the SUCS and ASSHTO systems, which facilitated the selection of the optimal binder percentage, together with the performance of a standard proctor test to determine the incorporation of the water content percentage. The Compressed Earth Blocks (CEB) were manufactured in a manual press with a 250x125x75 mm mold for hollow blocks, following guidelines established in previous studies. The initial dosage consisted of; soil (82.75%), sand (6.20%), and cement (11.03%). The innovation in this process was present in the modification of the standard composition by replacing the sand proportion with mining tailings in different percentages (1.55, 3.10, 4.65, and 6.20%). The evaluation of the mechanical behavior showed that all BTC met the minimum resistance standards according to the NTE INEN 294 regulations and that 8 of the 15 lots tested exceeded the 5 Mpa requirement for load-bearing walls, according to the NTE INEN 297. The results are encouraging and suggest the need for further research regarding the evaluation of other types of soils, their water percentage adoption, and binder selection. Keywords: Tailings, dosage, blocks, binder.